132k views
1 vote
(-6) - (7)(-4) +(5) + (-8)(-9)/(-3)(-2)

User Rafaela
by
5.5k points

1 Answer

5 votes

Answer:

75

Explanation:

Simplify the following:

-6 - 7 (-4) + 5 - 8×(-9)/(-3) (-2)

-8×(-9)/(-3) (-2) = (-8 (-9) (-2))/(-3):

-6 - 7 (-4) + 5 + (-8 (-9) (-2))/(-3)

(-9)/(-3) = (-3×3)/(-3) = 3:

-6 - 7 (-4) + 5 - 83 (-2)

-7 (-4) = 28:

-6 + 28 + 5 - 8×3 (-2)

-8×3 = -24:

-6 + 28 + 5 + -24 (-2)

-24 (-2) = 48:

-6 + 28 + 5 + 48

| 2 |

| 4 | 8

| 2 | 8

+ | | 5

| 8 | 1:

81 - 6

| 7 | 11

| 8 | 1

- | | 6

| 7 | 5:

Answer: 75

User JCBiggar
by
5.0k points